Extramedullary Intradural Spinal Tumors: a Review of Modern Diagnostic and Treatment Options and a Report of a Series - Kenan Arnautovic; Aska Arnautovic (Biomolecules & Biomedicine, 2009)
Extramedullary intradural spinal tumors are rare. Less than 15% of all central nervous system (CNS) tumors are spinal. Ninety percent of these patients are older than 20 years. Most of spinal tumors are extradural (50-55%) whereas 40-45% are intradural. Furthermore, 5% are intramedullary and 40% are extramedullary. Most common are Schwannomas (29%), followed by meningiomas (25%) and gliomas (22%).